TRANSFORMASI PRAKTIK AKREDITASI BAN-PDM MALUKU MELALUI PELATIHAN DARING DALAM PENERAPAN INSTRUMEN AKREDITASI TERBARU - Hamizar, Arizal; Wakano, Abidin; Hasanah, Nur; Marantika, Juliaans E.; Limba, Anatasija; Malasari, Dewi Qhuril; Matitaputty, Jenny Koce; Tamaela, Eduard Yohannis (MAJU : Indonesian Journal of Community Empowerment, 2024)
The purpose of this community service is to enhance the capacity of BAN-PDM assessors in Maluku Province through online training on the 2024 Accreditation Instrument. This training aims to deepen assessors' understanding of key aspects of educational accreditation, such as school climate, principal leadership, the role of educators, and the learning process. By integrating online methods, it is expected that this training can address the geographical challenges in the Maluku archipelago and improve the quality of educational accreditation in the region. The results of this training show that online methods are effective in enhancing assessors' understanding of the latest accreditation instruments. Despite facing technical challenges and connectivity limitations, participants demonstrated a significant increase in their understanding and skills related to educational accreditation. The evaluation of the training results indicates that assessors can effectively apply new knowledge in their accreditation practices, making a positive contribution to improving the quality of education in Maluku Province.